identify and find the relationship between the kinetic dispersion of the muscles and the kinetic reaction and performance of the kinetic formation on the balance beam device - م.م بيداء طارق ا.د هدى شهاب جاري ا.م.د وردة علي (physical education and sport sciences college for women/ Baghdad University, 2018)
The study is the importance of the reasons were uneven performance of female students during the technical performance on the balance beam device, When the movements lead to a kind of psychological changes Such as anxiety, dispersion, lack of attention, focus and the inclusion of muscle groups beyond the need for skill, which negatively affects the performance and thus reduce the final grade obtained by the student. The aim of the study was to identify and find the relationship between the kinetic dispersion of the muscles and the kinetic reaction and performance of the kinetic formation on the balance beam device, the researcher used the descriptive approach and the sample of the research was selected from the students of the second stage (62) students randomly. The tests used in the research included one of the psychological tests within the Vienna international system is the test of reaction and dispersion of the movement and test the performance of the kinetic array on the balance device. The researcher concluded that there is an adverse correlation between the variables of the research and concluded the need for integration between the speed of the motor response, the more affected the dispersion of the motor, which reflected negatively on performance and ensure the performance of the kinetic array on the balance-balance device to be at a high level should increase improvement in time of motor reaction and kinetic dispersion.